POLA INTERAKSI SPASIAL ANTARA KABUPATEN/ KOTA DI SUMATERA BARAT DENGAN KOTA PADANG - Novya Zulva Riani (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2012)
This research aims to identify patterns of spatial interaction between district/cities in West Sumatra with Padang, where the interaction pattern is divided into two parts: the spatial patterns of interaction in the form of passenger movement and spatial patterns of interaction in the form of vehicles movement to and from Padang. By using LQ analysis tools, odds movement and accessibility index concluded that passenger movement from Padang to the district / city in West Sumatra  converge towards Agam, Pasaman, East Pasaman, Tanah Datar, Sijunjung and Painan, and movement of vehicles converging towards Sawahlunto , Pariaman, Agam, Pasaman and East Pasaman. While the movement of passengers to Padang centralized Bukittinggi, Payakumbuh, Solok, Sawahlunto and Pariaman and movement of vehicles to Padang centralized Bukittinggi, Payakumbuh, Solok, Tanah Datar, Sijunjung and Painan. The largest odds movement in the form of spatial interaction is passenger movement and so vehicles movement between Padang to Pariaman.  The highest accessibility index is between Padang with pariaman, meaning between the two regions have a high level of ease movement